Evaluasi Tingkat Kepuasan Mahasiswa terhadap Kualitas Internet UIN Suska Riau Menggunakan Metode SERVQUAL dan CSI - Aulia, Rian; Saputra, Eki; Ahsyar, Tengku Khairil (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The human need for communication and information drives the rapid progress of communication and information facilities. The development of information technology in the current era of globalization is accelerating the progress of learning media. The use of information and communication technology as a learning medium has become a necessity. This research was conducted at the Sultan Syarif Kasim State Islamic University (UIN) Suska Riau which is located in Panam, Jl. HR. Soebrantas KM 15, Simpang Baru. The number of respondents in this study was 100 people. Based on the research conducted, it can be concluded that calculations using the service quality method produce five attribute statements with five internet quality dimensions. From the results obtained, these five dimensions have not been able to satisfy students because the quality value of each dimension is smaller than 1 (Q ≤ 1). Therefore, improvements are needed by the campus as a recommendation to improve internet quality.